A domino effect in drug action: from metabolic assault towards parasite differentiation - Haanstra, Jurgen R.; Kerkhoven, Eduard J.; Tuijl, Arjen van; Blits, Marjolein; Wurst, Martin; Nuland, Rick van; Albert, Marie-Astrid; Michels, Paul A. M.; Bouwman, Jildau; Clayton, Christine; Westerhoff, Hans V.; Bakker, Barbara M. (Molecular microbiology, 2011)
Awareness is growing that drug target validation should involve systems analysis of cellular networks. There is less appreciation, though, that the composition of networks may change in response to d...